Jingang Qigong. Ejercicios de Respiración Chi Kung - Prat González, Joan (Revista de Artes Marciales Asiáticas, 2012)
<span style="mso-ascii-font-family: Calibri; mso-fareast-font-family: Calibri; mso-hansi-font-family: Calibri; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: PT-BR; mso-bidi-font-weight: bold;" lang="PT-BR">Shao-ch'ing Yang. Madrid: Miraguano, 1990. 112 páginas. 19x13 cm. I.S.B.N.: 84-85639-68-5.